Pharmacological treatment options for cognitive dysfunction induced by multiple sclerosis: a network meta-analysis - Fan, Zhuyuan; Liu, Dan; Zhang, Guangwei; Guo, Xinlin (Frontiers in Neurology, 2025)
ObjectivesTo compare the effects of various pharmacological treatments on partial test results and adverse effects in patients with cognitive dysfunction (CD) induced by multiple sclerosis (MS) through a network meta-analysis.MethodsPubMed, Embase, Cochrane Library, and Web of Science databases were systematically retrieved for randomized controlled trials (RCTs) evaluating the influence of different pharmacological treatments on CD in MS patients. The search was updated until October 8, 2024. The Risk of Bias tool was used to assess the quality of eligible studies, and R was employed for data analysis.ResultsTwenrt six studies involving 23,839 MS patients were included for our analysis. Network meta-analysis results indicated that compared to placebo, L-amphetamine may improve memory in MS-induced CD. Memantine may enhance performance on the Paced Auditory Serial Addition Test (PASAT). Compared to memantine, fampridine-SR, ginkgo biloba, and melatonin showed inferior effects. Atomoxetine may improve Symbol Digit Modalities Test (SDMT) scores, outperforming donepezil, ginkgo biloba, L-amphetamine, modafinil, and rivastigmine. Additionally, atomoxetine may improve California Verbal Learning Test (CVLT) performance, compared to ginkgo biloba, L-amphetamine, and memantine. In terms of adverse effects, rivastigmine was less likely to cause dyspepsia.ConclusionBased on current evidence, L-amphetamine may improve memory in MS-induced CD. Melatonin may enhance PASAT performance, and atomoxetine may improve both SDMT and CVLT scores in these patients. However, rivastigmine was found to have a lower likelihood of causing dyspepsia among the treatments assessed.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024623642.